A guide to epidural management. (2nd January 2020) - McLaren, Steve; Hughes, Megan; Sheehan, Catherine; Sokhi, Jagdish
Abstract : Epidural analgesia is a key component in the management of inpatient pain relief, particularly in surgical and trauma patients, and those with comorbidities. When used appropriately epidurals can decrease a patient's opiate consumption, as well as reducing the risk of adverse cardiorespiratory outcomes. To non-anaesthetists, or those not versed in their usage, epidurals can appear complex and intimidating, and the potential complications, although rare, can be catastrophic if not picked up on in a timely fashion. This article demystifies the epidural for hospital clinicians, looking at the anatomy and pharmacology, helping to identify patients who may benefit from epidural analgesia, highlighting some common pitfalls and questions posed by nursing staff, and providing a framework via which junior clinicians can detect, manage and appropriately escalate epidural-related problems and complications. Epidural analgesia is an invasive and high-risk intervention; as such it should always be managed by a multidisciplinary team, including anaesthesia and acute pain services.